Comprehensive control for unified power quality conditioners - Miguel OCHOA-GIMÉNEZ; Aurelio GARCÍA-CERRADA; Juan Luis ZAMORA-MACHO (Journal of Modern Power Systems and Clean Energy, 2017)
Abstract This paper presents a comprehensive control strategy for unified power quality conditioners (UPQCs) to compensate for both voltage and current quality problems. The controllers for the series and shunt components of the UPQC are, equally, divided into three blocks: ① main controller, which deals with the fundamental-frequency issues such as active and reactive power flow; ② harmonic controller, which ensures zero-error tracking while compensating voltage and current harmonics; ③ the set-point generation block, which handles the different control objectives of the UPQC. The controller design procedure has been simplified to the selection of three parameters for each converter. Furthermore, the proposed strategy can be implemented measuring only four variables, which represents a reasonable number of sensors. In addition, a pulse width modulation (PWM)-based modulation with fixed switching frequency is used for both converters. The proposed control strategy has been validated experimentally under different conditions, including grid-frequency variations.